KENNA AND LEDGER’S SINCERE FEELINGS WITHIN FORGIVENESS IN COLLEEN HOOVER’S NOVEL REMINDERS OF HIM - Johanes Claudio Perdana Napitupulu; Yasmine Azzah Adillah Wirnoto; Raydzal Wibowo Sabandar Putra; Dwiky Jibril Aulia Baskara; Cahyaningsih Pujimahanani; Rommel Utungga Pasopati (Seminar Nasional Hasil Riset dan Pengabdian, 2025)
This study explores Kenna and Ledger’s sincere feelings reflected in their process to forgive in a novel entitled Reminders of Him by Colleen Hoover in 2022. The authors on this article use qualitative method which can help the readers to explore more about the contexts of the object. This forgiveness shows how Kenna and Ledger can forgive each other and move forward into better future through sincere feelings. The analysis investigates how Kenna tries to reach forgiveness in order to escape from her past memories while Ledger wants Kenna forgive him for what he has done to her. Both of them keep exchanging sincere feelings so that such forgiveness can always be realized for better future. In conclusion, the authors confirm that Kenna and Ledger indicate sincere feelings within their relationship while forgiving each other and moving forward.